Criminal Thinking Patterns: Are Child Molesters Unique? - Huss, Matthew T.; Baumgartner, Jerome V.; Scalora, Mario J. (International journal of offender therapy and comparative criminology, 2001)
This study examined the ability of the Psychological Inventory of Criminal Thinking Styles (PICTS) to reliably differentiate between men with and without histories of child molestation crimes at a maximum-security state hospital forensic mental health unit. Results showed that as hypothesized, molesters (n = 28) were less likely than non-sex offenders (n = 35) to exhibit thinking errors captured by the Cutoff, Entitlement, and to a lesser extent, the Cognitive Indolence, Discontinuity, and Power Orientation scales of the PICTS. The findings support its use in targeting general criminal thinking errors for treatment in mixed-offender populations, as well as its use in sex offender populations to augment other sex offense cognitive distortion measures when designing treatment